2014
DOI: 10.1021/jp505304n
|View full text |Cite
|
Sign up to set email alerts
|

Applications of a Bis-Urea Phenylethynylene Self-Assembled Nanoreactor for [2 + 2] Photodimerizations

Abstract: Confined environments can be used to alter the selectivity of a reaction by influencing the organization of the reactants, altering the mobility of trapped molecules, facilitating one reaction pathway or selectively stabilizing the products. This manuscript utilizes a series of potentially photoreactive guests to interrogate the utility of the one-dimensional nanochannels of a porous host to absorb and facilitate the reaction of encapsulated guests. The host is a columnar self-assembled phenylethynylene bis-ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…Previous work demonstrated that the $0.9 nm diameter nanochannels of the self-assembled phenylethynylene bis-urea host are accessible to gases including Xe and CO 2 [27,30]. The channels can also accommodate a range of organic guests including coumarins, acenaphthylene and stilbenes [21,27]. Confinement of guests within the nanochannels of host 1 facilitated the selective [2 + 2] photodimerization reactions of coumarin, 6-methyl coumarin, 7-methyl coumarin and acenaphthylene in good conversion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work demonstrated that the $0.9 nm diameter nanochannels of the self-assembled phenylethynylene bis-urea host are accessible to gases including Xe and CO 2 [27,30]. The channels can also accommodate a range of organic guests including coumarins, acenaphthylene and stilbenes [21,27]. Confinement of guests within the nanochannels of host 1 facilitated the selective [2 + 2] photodimerization reactions of coumarin, 6-methyl coumarin, 7-methyl coumarin and acenaphthylene in good conversion.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, stilbenes and 7-methoxy coumarin were unreactive. We turned to GCMC simulations to probe the origin of these changes in reactivity and selectivity, which afforded good predictions for these simple aromatic guests [27]. Here, we test utility and scope of the previously employed GCMC simulation protocol to predict if chromone and its derivatives (1) will be absorbed by this host and (2) will be reactive inside the confined space of the host.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5À12 Phenylether bis-urea (1) and phenylethynylene bis-urea (2) self-assemble into similar columnar structures held together by hydrogen bonds with distances of 2.85À3.05 Å, which set a repeat distance of between 4.6 and 4.7 Å. 6,10 The cross-sectional size and shape of the columns differ as they are precisely determined by the molecular structure of the macrocycle building blocks. In 1, the cavity is seen to be roughly elliptical in shape with cross-sectional dimensions of ∼4.8 Å Â 3.7 Å, while in 2, the pore space cross-section is almost round with a diameter of ∼9 Å.…”
mentioning
confidence: 99%